Pengaruh Inflasi, PDRB dan Upah Minimum terhadap Penyerapan Tenaga Kerja di Provinsi Sulawesi Selatan - Ana Ramadhani. A; Basri Bado; Sri Astuty; Muhammad Syafri; Irwandi (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of inflation, Gross Regional Domestic Product, and minimum wage on labor absorption in South Sulawesi Province. Labor absorption is used as the dependent variable and is measured by the number of employed people, while inflation, Gross Regional Domestic Product, and minimum wage are used as independent variables measured by the annual inflation rate, constant price regional output, and the applicable minimum wage in each region. The population of this study consists of secondary data related to these variables in Makassar City, Palopo City, Bone Regency, and Parepare City during the 2015–2024 period. The data were obtained from official publications of Statistics Indonesia and the Department of Manpower of South Sulawesi Province. The sample was selected purposively because these regions represent major economic centers in the provincial economic system and provide complete and consistent data. Panel data regression analysis was employed to examine the relationship between variables. The results show that inflation does not have a significant partial effect on labor absorption, while Gross Regional Domestic Product and minimum wage have a positive and significant effect. Simultaneously, the three variables significantly influence labor absorption, indicating that regional economic growth and wage policies play an important role in increasing employment opportunities in South Sulawesi Province.